A molecular dynamics study on the mechanism of heterogeneous bubble nucleation of mixed liquid. (November 2022) - Liu, Liang; Sun, Chongzheng; Li, Yuxing; Han, Hui; Zhu, Jianlu; Su, Zhengxiong
Abstract: The nucleate boiling of mixed boiling is widely utilized in natural gas, hydrogen liquefaction process, and other fields. In this paper, the molecular dynamics study of heterogeneous bubble nucleation of pure argon liquid and the argon‑krypton mixed liquid on the platinum surface was conducted. The nucleate boiling characteristics were presented and the variations of the density, temperature, nucleation embryo volume, and heat flux were analyzed. The difference in the nucleation mechanism of pure liquid and mixed liquid was explained based on the competition of atomic potential energy and atomic kinetic energy. The effect of the component mole fraction on the bubble nucleation of mixed fluid was also discussed. The results showed that the onset superheat of boiling of argon‑krypton mixed liquid is higher than that of pure argon. The higher the mole fraction of the component with a lower saturation temperature, the lower the onset superheat of the liquid nucleate boiling. When x  < 0.5, the growth rate of the nucleation embryo is dominated by the x value, when x  > 0.5, the growth rate is dominated by wall temperature. Moreover, the difference in diffusion coefficients of each component is one of the direct causes of determining the growth rate of nucleation embryos. The findings provide insights into the mechanisms of differences in boiling nucleation between mixed liquid and pure liquid, as well as guide the reasonable utilization of mixed liquid. Highlights: A molecular dynamics study of heterogeneous bubble nucleation is conducted. The bubble nucleation mechanism of the mixed liquid is analyzed. The greater energy parameter of the component, the higher superheat. The boiling performance increases with increasing mole fraction of argon.